Obstructive Sleep Apnoea and Type 1 Diabetes Mellitus: A Neglected Relationship? - Panou, Theodoros; Roukas, Konstantinos; Chadia, Konstantina; Nena, Evangelia; Gouveri, Evanthia; Papanas, Nikolaos; Steiropoulos, Paschalis (Experimental and Clinical Endocrinology & Diabetes, 2024)
Obstructive sleep apnoea (OSA) is regarded as a major health condition, progressively affecting an increased number of people around the world. The interplay between OSA and type 2 diabetes mellitus (T2DM) has been extensively studied. However, little is known about the relationship between OSA and type 1 diabetes mellitus (T1DM). This review provides insight into the prevalence of OSA in T1DM and its relationship with diabetic complications. Studies have hitherto yielded contradictory results on the occurrence of OSA in T1DM. Indeed, the risk of OSA in T1DM has ranged from 1 in 10 to more than 1 in 2 T1DM subjects. This high occurrence was confirmed by objective polysomnography as well as widely used subjective questionnaires. Multiple studies revealed the important correlation between OSA and diabetes complications. Both microvascular (nephropathy, neuropathy and retinopathy) and macrovascular complications appear to be associated with OSA occurrence, although some associations were not significant due to inadequate data. In conclusion, T1DM subjects carry a higher risk of undiagnosed OSA. Additional studies are needed to clarify the exact correlation between the two conditions.
Keywords: OSA; T1DM; diabetic complications